Penggunaan Komunikasi Non-Verbal Dalam Bertukar Informasi Ketika Berkendara Bersama Dikalangan Anggota Forum Nusantaride - Aditya Marsela (JURNAL PURNAMA BERAZAM, 2020)
Nonverbal communication is a communication which the message delivered does not use words, and is a process of communicating information using behavior. Nonverbal communication is an important aspect of group life as information is conveyed. Nonverbal communication can also be referred to as body language messages, through body movements, hand movements, and leg movements, and other movements. Therefore nonverbal communication can assist an motorcycle organizations in conveying information while driving. In this case the author will research the functions and forms of nonverbal communication within the Nusantride motorcycle riders forum. The research method used in this study was a descriptive qualitative method and the technique used in data collection was observation and interviews with five respondents who were members of the Nusantaride forum with a random sampling system. Based on the results of the study, nonverbal communication carried out by Nusantarie forum members in general provides a good and important function for forum members.